2021
DOI: 10.1136/bmjgh-2021-005877
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intermittent preventive treatment in pregnancy with sulphadoxine-pyrimethamine (IPTp-SP) in Ghana

Abstract: IntroductionGhana adopted the revised WHO recommendation on intermittent preventive treatment in pregnancy using sulfadoxine-pyrimethamine (IPTp-SP) in 2012. This study has assessed the effectiveness and safety of this policy in Ghana.MethodsA total of 1926 pregnant women enrolled at antenatal care (ANC) clinics were assessed for birth outcomes at delivery, and placental histology results for malaria infection were obtained from 1642 participants. Association of reduced placental or peripheral malaria, anaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
(31 reference statements)
0
12
2
Order By: Relevance
“…Our results are in line with other studies that have shown a positive impact of monthly SP on maternal malaria during pregnancy compared with the two-dose SP regimen. 11 , 23 , 24 We have not found studies that looked at the impact of monthly SP during the second and third trimesters separately, but there is no biological reason to believe the results would differ from our findings. Although azithromycin has some antimalarial activity, 25 previous results about the impact of azithromycin on malaria are mixed, with some studies indicating a reduction in malaria 26 28 and some studies suggesting no impact.…”
Section: Discussioncontrasting
confidence: 80%
“…Our results are in line with other studies that have shown a positive impact of monthly SP on maternal malaria during pregnancy compared with the two-dose SP regimen. 11 , 23 , 24 We have not found studies that looked at the impact of monthly SP during the second and third trimesters separately, but there is no biological reason to believe the results would differ from our findings. Although azithromycin has some antimalarial activity, 25 previous results about the impact of azithromycin on malaria are mixed, with some studies indicating a reduction in malaria 26 28 and some studies suggesting no impact.…”
Section: Discussioncontrasting
confidence: 80%
“…This difference can be due to the low distribution of mosquito nets to pregnant women during Antenatal Consultation and the absence of mosquito net distribution campaigns. These results are higher than the 35.5% obtained by Dosoo DK, et al [29] 2021 in Ghana.…”
Section: Association Between Anemia and Characteristics Of The Study ...contrasting
confidence: 59%
“…This reduction in infection numbers itself (i.e. about 20% prevalence of parasitaemia prior to commencement of IPTp-SP [28] against about 3% prevalence at delivery [30] in the study area) suggests the effectiveness of IPTp-SP in clearing P. falciparum infections during pregnancy. Also, DNA could not be amplified in a substantial number of DBS, possibly due to DNA degradation.…”
Section: Plos Onementioning
confidence: 81%
“…This study was part of a trial that evaluated the effectiveness of four or more doses of IPTp-SP in the middle belt of Ghana. Dried blood spot (DBS) samples from a cohort of pregnant women were collected at their first antenatal care (ANC) clinic visit (prior to administration of IPTp-SP) [28] and at delivery [30] to determine the prevalence of molecular markers of resistance to SP.…”
Section: Study Area Participants and Sample Collectionmentioning
confidence: 99%